2015
DOI: 10.1177/0300060514561136
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of copeptin, C-reactive protein and procalcitonin are positively correlated with APACHE II scores in patients with sepsis

Abstract: Objective: To evaluate the correlation between Acute Physiology and Chronic Health Evaluation II (APACHE II) score and plasma concentrations of copeptin, C-reactive protein (CRP) and procalcitonin in patients with sepsis. Methods: Patients with sepsis were prospectively enrolled. APACHE II scores were determined during the first 24 h after admission to the intensive care unit. Plasma copeptin, CRP and procalcitonin were quantified at admission, 24 h, 48 h, and 72 h. Survival at 28 days after admission was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
(36 reference statements)
3
23
1
Order By: Relevance
“…[2225] The role of CRP and PCT as potential biomarkers for infection has been unclear since earlier studies showed inconsistent results. [20,21,26,27] In our study, we found no association between CRP and PCT and sepsis-related mortality in pediatric patients. This lack of association could have been because all study participants suffered from severe infections.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…[2225] The role of CRP and PCT as potential biomarkers for infection has been unclear since earlier studies showed inconsistent results. [20,21,26,27] In our study, we found no association between CRP and PCT and sepsis-related mortality in pediatric patients. This lack of association could have been because all study participants suffered from severe infections.…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, the CRP was also included in the multivariate logistic regression. [20,21] The Hosmer–Lemeshow test was used to assess the goodness-of-fit of the logistic regression models. After the logistic regression equation was established, the logit probabilities of patients from both groups were calculated to verify internal and external validity.…”
Section: Methodsmentioning
confidence: 99%
“…[18] In a small study evaluating 41 septic patients a strong correlation between copeptin and the disease severity score APACHE II was demonstrated. [19] In our cohort, only weak correlations between copeptin and APACHE II scores, as well as other established scores including the SAPS II and the SOFA score were demonstrated. Considering acute heart failure, several studies demonstrated elevated levels of copeptin being predictive of mortality, such as a substudy of the BACH study, including 557 patients with AHF.…”
Section: Discussionmentioning
confidence: 56%
“…It is present in low levels in the blood of healthy subjects. Recently, CRP and PCT have been investigated for potential to serve as important tools for the early diagnosis of bacterial infection in clinical applications (11,12).…”
Section: Introductionmentioning
confidence: 99%